2014
DOI: 10.1016/j.aller.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative allergic reactions: Experience in a Flemish referral centre

Abstract: NMBA, antibiotics, latex and chlorhexidine were the main culprits of IgE-mediated perioperative reactions. Uncertainties remain concerning the specificity and sensitivity of skin testing. Tryptase assays can be useful in the discrimination of IgE and non-IgE-mediated reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 27 publications
4
37
0
1
Order By: Relevance
“…It would be useful to separate the administration of the prophylactic antibiotic therapy and anaesthetic induction in order to identify and treat the reaction as early as possible. Betalactams are responsible for 70% of reactions due to antibiotics [20], especially cephalosporins [5], being cefazolin the most frequent causal agent in Spain [66]. Vancomycin is the second most common antibiotic involved, although reactions are almost always due to a non-immunological mechanism [67].…”
Section: A) Drugsmentioning
confidence: 99%
“…It would be useful to separate the administration of the prophylactic antibiotic therapy and anaesthetic induction in order to identify and treat the reaction as early as possible. Betalactams are responsible for 70% of reactions due to antibiotics [20], especially cephalosporins [5], being cefazolin the most frequent causal agent in Spain [66]. Vancomycin is the second most common antibiotic involved, although reactions are almost always due to a non-immunological mechanism [67].…”
Section: A) Drugsmentioning
confidence: 99%
“…The proportion of patients in our study for whom no causative agent could be determined was comparable to those in other reports. [12][13][14] Among the 21 patients who suffered anaphylaxis during anaesthesia and the cause was subsequently identified, antibiotics were the most common causative agent (52.3%), followed by NMBAs (38.1%), opioids (4.8%) and gelofusine (4.8%). In contrast, data from 4000 patients reported by Mertes et al indicated that NMBAs accounted for 63% of reactions, followed by latex (14%), hypnotics (7%), antibiotics (6%), plasma substitutes (3%) and opioids (2%).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this enzyme is therefore a key element in diagnosing anaphylactic reactions [19]. However, the optimum number of Tryptase measurements and the best interpretative strategy has not yet been established in perioperative anaphylaxis [20][21][22]. Our internal protocol for Anaphylaxis in the perioperative period includes a proposal for Tryptase measurements.…”
Section: Discussionmentioning
confidence: 99%